High temperature ignition delay time of DME/n-pentane mixture under fuel lean condition. (1st March 2017) - Jiang, Xue; Deng, Fuquan; Yang, Feiyu; Zhang, Yingjia; Huang, Zuohua
Highlights: New ignition delay time data of DME/ n -pentane/O2 /Ar mixtures were provided. Five literature models were validated against the experimental data. Effects of DME addition on n -pentane ignition delay times were investigated. Abstract: Ignition delay times were measured behind reflect shock waves for the lean DME/ n -pentane fuel blends with DME blending ratios from 0% to 100% over a wide range of conditions: pressures from 2 to 20 atm, temperatures from 1100 to 1600 K and equivalence ratio of 0.5. Correlations of ignition delay times of DME/ n -pentane were deduced from the experimental data using multiple linear regression. Comparison between measured ignition delay times and numerical predictions by five available kinetic mechanisms, namely NUI Galway pentane isomer model, JetSurF2.0 model, LLNL n -alkanes Model, NUI Galway Mech_56.54 Model and Wang's DME model, were conducted. NUI Galway pentane isomer model shows good predictions for ignition delay times of DME, n -pentane and their blends which was conducted in this study to interpret the effect of DME addition on the ignition chemistry of n -pentane.